Improved technical characteristics of the Mi-8/17 in the Army of FYR Macedonia - Petreski, Drage T.; Iliev, Andrej P.; Trajanovska, Elena M.; Gjurov, Lazar B.; Petrovski, Aleksandar S. (Vojnotehnički glasnik / Military Technical Courier, 2017)
Worldwide experience has shown that MI-8/17 helicopters are on the top of the middle class list of high performance multipurpose helicopters, flying at high altitudes in complex meteorological conditions. The paper addresses their development, transport, as well as rescuing and combat capabilities. The excellent technical characteristics of flight and their capabilities for uninterrupted and smooth performance of tasks demonstrate the reason why the Armed forces of the FYR of Macedonia decided to use Mi-8/17 helicopters and are determined to invest in their modernization and improvement of their technical capabilities. The modernization of the resources of armies is a continuous process, which is a part of all modern military security structures. Most armed forces do not economize the funds allocated for this purpose, due to the fact that they aspire to achieve the planned capabilities, so that they would attain the ultimate preparedness in terms of capabilities of the security forces regarding technology and trained personnel.